Rozwiąż równania:
a) 2x + 17 = 26-X
b)7x - 6 = - 6x +7
c) -7(2x + 1) = 4
d) x ( x + 2) = x2 + 5x – 24
e) 2x - (1 - 4x) =2 + ( 8x – 5)
f) 4-2(5 - x) = x - 4(x - 1)
g)7 - ( 3x + 4) = ( x +1 ) - ( 2x + 4)
h)2(x-8) + (4-11x) = - 3(2x - 1) - (x + 4)​



Odpowiedź :

Odpowiedź:

a)2x+17=26-x

2x+x=26-17

3x=9/:3

x=3

b)7x-6=-6x+7

7x+6x=7+6

13x=13 /:13

x=1

c)-7(2x+1)=4

-14x+-7=4

-14x=4+7

-14x=11 /:14

x=-11/14

d)x(x+2)=2x+5x-24

2x+2x=9x-24

4x-9x=-24

-5x=-24 /:-5

x=4,8

e)2x - (1 - 4x) =2 + ( 8x – 5)

2x+4x-1=-3+8x

6x-1=-3+8x

6x-8x=-3+1

-2x=-2/:-2

x=1

f)4-2(5 - x) = x - 4(x - 1)

4-10-2x=x-4x-4

-6-2x=x-4x-4

-2x-x+4x=-4+6

x=2

g)7 - ( 3x + 4) = ( x +1 ) - ( 2x + 4)

3-3x=3x-5

-3x-3x=-5-3

-6x=-8/:-6

x=1 1/3

( jeśli od d są źle zrobione to przepraszam pozdrawiam.)

Odpowiedź:

a) 2x+x=26-17

3x=9

x=3

b)7x+6x=7+6

13x=13

x=1

c)-14x-7=4

-14x=4-7

-14x=-3

14x=3

x=4 2/3

d)x²+2x=x²+5x-24

x²-x²+2x-5x=-24

-3x=-24

x=8

e)2x-1+4x=2+8x-5

2x+4x-8x=2-5+1

-2x=-2

x=1

f)4-10+2x=x-4x+1

4-10-1=x-4x-2x

-7=-5x

-5x=-7

x=7/5=1 2/5

g)7-3x-4=x+1-2x-4

7-4-1+4=x-2x+3x

6=2x

2x=6

x=3

h)2x-16+4-11x=-6x+3-x-4

2x-11x+6x+x=16-4+3-4

-2x=11

x=-11/2=-5 1/2

Szczegółowe wyjaśnienie: